Drug utilization study of drugs prescribed in patients suffering from chronic obstructive pulmonary disease attending the pulmonary medicine outpatient department of a tertiary care hospital-an observational study - Chaware, Akshay A.; Khobragade, Akash A.; Joshi, Abhijeet; Bodkhe, Prachi B.; Gaidhane, Sanket S.; H. V., Likith; Chavan, Monisha S. (International Journal of Basic & Clinical Pharmacology, 2025)
Background: Chronic obstructive pulmonary disease (COPD) is a progressive respiratory disorder requiring long-term pharmacological management. This study aimed to evaluate prescription patterns, drug utilization, polypharmacy and cost analysis in COPD patients attending the outpatient department of a tertiary care hospital. Methods: This single-center, cross-sectional observational study was conducted in collaboration with the Department of Pulmonary Medicine. A total of 600 prescriptions of COPD patients were analyzed over 18 months (January 2020–June 2021) following WHO guidelines for Drug Utilization Studies. Adult patients diagnosed with COPD and attending the outpatient department were included. Data on demographics, drug classes, fixed-dose combinations (FDCs), essential drug listing and cost burden were collected and analyzed using descriptive statistics. Results: The average age of patients was 62.87±14.52 years, with 84.67% being male. A total of 3815 drugs were prescribed, with bronchodilators (62.70%) being the most common class, followed by corticosteroids (8.10%). Tiotropium bromide and Salbutamol were the most frequently used individual drugs. The average number of drugs per prescription was 6.36±2.31, indicating polypharmacy. Fixed-dose combinations such as Theophylline+Etophylline (41.87%) were commonly prescribed. The average prescription cost was 647.23 INR, of which 44.90% was borne by patients. Most drugs (69.78%) were prescribed by generic names and 62.43% were from the National Essential Medicines List. Conclusions: This study highlights a significant degree of polypharmacy and suggests that while prescribing trends largely align with GOLD guidelines, greater access to essential drugs through hospital pharmacies and efforts to reduce patient cost burden are warranted.